2021
DOI: 10.47405/mjssh.v6i9.998
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors to Decline in Physical Activity Among Adolescents: A Scoping Review

Abstract: It is presumed that the level of physical activity (PA) declines during a person’s lifespan, particularly during adolescence. The main objective of this scoping review is to summarize and identify the current literature that addresses contributing factors related to adolescent physical inactivity. This scoping review was carried out using the framework suggested by Arskey and O'Malley. The literature review was undertaken using the reference period between 2008 and 2014, based primarily on the PubMed, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Behavioral change: PA interventions can focus on helping adolescents to change their behavior and become more active. This can include setting goals, providing support, and tracking progress [19].…”
Section: Resultsmentioning
confidence: 99%
“…Behavioral change: PA interventions can focus on helping adolescents to change their behavior and become more active. This can include setting goals, providing support, and tracking progress [19].…”
Section: Resultsmentioning
confidence: 99%
“…Behavioral change: PA interventions can focus on helping adolescents to change their behaviour and become more active. This can include setting goals, providing support, and tracking progress (Ahmad, N.F. et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Leriche and Walczak (2014) observed that 37.2% of their sample of 1886 college students spent less than 10 minutes of PA per week outside of class. Similarly, several authors report a drastic decrease in PA practice at the end of adolescence, during the transition to adulthood (Ahmad et al, 2021;Castro et al, 2020;Poriau & Delens, 2017;Statistics Canada, 2021a;Wilson et al, 2021) as well as a deterioration of physical fitness among students (Chiasson, 2004;Lemoyne & Girard, 2018;Leone et al, 2023). Although students who take a PEH class do more PA than those who do not (Lemoyne, 2012), once all required PEH courses are completed, there is a significant decrease in PA practice (Poriau & Delens, 2017).…”
Section: Introductionmentioning
confidence: 99%